RISK FACTORS AFFECTING THE MENTAL HEALTH OF FREQUENTLY ILLNESSES PRESCHOOL CHILDREN - Rakhimova Durdona Jurakulovna; Nigora Abdurakhmanovna Utamuradova (Western European Studies, 2024)
It is known that the level of influence of various factors on a child's health changes in different periods of child development. The child's body develops under the interaction of biological and social factors, and their proportions are not the same at different age stages. A complex continuum of influences occurs, with a genetic basis predominating in some cases and environmental influences in others. V.V. In the work conducted under the leadership of Kovalyov (1989), it was determined that two groups of risk factors influence the development of neuropsychiatric diseases. The risk factors of the first group include a pre-morbid condition in the form of mental dissontogenesis, which does not correspond to the scope of specific psychopathological syndromes, disharmony of personality formation and partial developmental delay. Exogenous risks (mental injury, parental alcoholism, parental defects), as well as perinatal pathology, brain infections, chronic somatic diseases, etc. are classified as secondary risk factors
Keywords: frequent patients; children; mental health; health